PENGURANGAN BEBAN TAS PUNGGUNG MENURUNKAN AKTIVITAS LISTRIK OTOT PUNGGUNG PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - Khrisna, A. A. Parama Swari; Griadhi, I Putu Adiartha (E-Jurnal Medika Udayana, 2015)
BACKPACK LOAD REDUCTION DECREASE D THE ELECTRICAL ACTIVITY OF THE STUDENTS BACK MUSCLES IN MEDICAL FACULTY UDAYANA UNIVERSITY Back muscle fatigue often occur at the student as a result of the heavy backpack used. Electromyography test has been conducted to provide a description of back muscle electrical activity that occurs in students. This study aims to investigates the influence of backpack used to electrical activity of the students back muscles in medical faculty udayana university. Has carried out a research with treatment by subject design in Medical Faculty Udayana University students. This study used 17 subjects (mean body mass : 52.59 ± 2.74 kg). This study was conducted first with measure the upper trapezius and erector spine muscles electrical activity with electromyography when the subjects wear the backpack with load 15% of body mass (measure A), then remeasurement when the subjects wear the backpack with load 10% of body mass (measure B). The results showed that backpack used with light load have a significant value statistically to decreased electrical activity of upper trapezius and erector spine muscles (p = 0,000).
Keywords: Electrical activity of muscle; electromyography; backpack